Effects of hydroxyurea treatment for patients with hemoglobin SC disease. Issue 2 (February 2016) - Luchtman‐Jones, Lori; Pressel, Sara; Hilliard, Lee; Brown, R. Clark; Smith, Mary G.; Thompson, Alexis A.; Lee, Margaret T.; Rothman, Jennifer; Rogers, Zora R.; Owen, William; Imran, Hamayun; Thornburg, Courtney; et al.
Abstract : Although hemoglobin SC (HbSC) disease is usually considered less severe than sickle cell anemia (SCA), which includes HbSS and HbS/β 0 ‐thalassemia genotypes, many patients with HbSC experience severe disease complications, including vaso‐occlusive pain, acute chest syndrome, avascular necrosis, retinopathy, and poor quality of life. Fully 20 years after the clinical and laboratory efficacy of hydroxyurea was proven in adult SCA patients, the safety and utility of hydroxyurea treatment for HbSC patients remain unclear. Recent NHLBI evidence‐based guidelines highlight this as a critical knowledge gap, noting HbSC accounts for ∼30% of sickle cell patients within the United States. To date, only 5 publications have reported short‐term, incomplete, or conflicting laboratory and clinical outcomes of hydroxyurea treatment in a total of 71 adults and children with HbSC. We now report on a cohort of 133 adult and pediatric HbSC patients who received hydroxyurea, typically for recurrent vaso‐occlusive pain. Hydroxyurea treatment was associated with a stable hemoglobin concentration; increased fetal hemoglobin (HbF) and mean corpuscular volume (MCV); and reduced white blood cell count (WBC), absolute neutrophil count (ANC), and absolute reticulocyte count (ARC). Reversible cytopenias occurred in 22% of patients, primarily neutropenia and thrombocytopenia. Painful events were reduced with hydroxyurea, more in patients >15 years old. These multicenter data support the safety and potentially salutary effects of hydroxyurea treatment for HbSC disease; however, a multicenter, placebo‐controlled, Phase 3 clinical trial is needed to determine if hydroxyurea therapy has efficacy for patients with HbSC disease. Am. J. Hematol. 91:238–242, 2016. © 2015 Wiley Periodicals, Inc.